Epidemiology and Antimicrobial Resistance of Stenotrophomonas maltophilia in China, 2014–2021 - Hanli Wang; Shirong Li; Haoyu Ji; Yixin Hu; Susheng Zhou; Xingwu Chen; Zhiwei Lu; Qinghai You; Yusheng Cheng; Lei Zha (Infectious Diseases and Therapy)
Abstract Introduction Stenotrophomonas maltophilia is an opportunistic pathogen associated with various nosocomial infections and is known for its intrinsic multidrug resistance. This study aims to provide a comprehensive overview of the epidemiology and resistance patterns of S. maltophilia in China from 2014 to 2021. Methods Data were extracted from the China Antimicrobial Resistance Surveillance System (CARSS) and the Blood Bacterial Resistance Investigation Collaborative System (BRICS), encompassing 1412 medical institutions across 31 provinces in China. We analyzed the prevalence of S. maltophilia in clinical isolates, focusing on specific patient populations and departments, as well as resistance profiles to recommended first-line antibiotics, including sulfamethoxazole-trimethoprim, levofloxacin, and minocycline. Results A total of 514,768 S. maltophilia strains were analyzed. The overall prevalence of S. maltophilia among all clinical bacterial isolates remained stable at approximately 2.1%, with higher rates observed in intensive care units and elderly patients. Resistance rates to sulfamethoxazole-trimethoprim decreased from 9.8% in 2014 to 7.5% in 2021. In contrast, resistance to levofloxacin showed a slight upward trend, increasing from 8.5% in 2014 to 9.5% in 2021. Meanwhile, minocycline resistance remained low, fluctuating marginally from 2.7% in 2014 to 1.7% in 2021. Conclusions This study highlights the stable prevalence of S. maltophilia in clinical settings in China and the overall low resistance rates to recommended first-line antibiotics. However, alarmingly high resistance rates were observed in specific specimen types, particularly in blood cultures, suggesting that minocycline may be the only reliable therapeutic option among the six tested antibiotics for treating such infections in China. Continuous surveillance and effective infection control measures are essential to manage S. maltophilia infections, particularly in vulnerable populations. Future research should focus on measuring the true burden of these infections and monitoring the susceptibility of the newly introduced antibiotics, such as cefiderocol.